A Community-Based Multicenter Trial of Pharmacokinetically Guided 5-Fluorouracil Dosing for Personalized Colorectal Cancer Therapy. (12th August 2014) - Patel, Jai N.; O'Neil, Bert H.; Deal, Allison M.; Ibrahim, Joseph G.; Sherrill, Gary B.; Olajide, Oludamilola A.; Atluri, Prashanti M.; Inzerillo, John J.; Chay, Christopher H.; McLeod, Howard L.; Walko, Christine M.
Abstract: Background: Pharmacokinetically guided (PK-guided) versus body surface area-based 5-fluorouracil (5-FU) dosing results in higher response rates and better tolerability. A paucity of data exists on PK-guided 5-FU dosing in the community setting. Patients and Methods: Seventy colorectal cancer patients, from one academic and five community cancer centers, received the mFOLFOX6 regimen (5-FU 2, 400 mg/m 2 over 46 hours every 2 weeks) with or without bevacizumab at cycle 1. The 5-FU continuous-infusion dose was adjusted for cycles 2–4 using a PK-guided algorithm to achieve a literature-based target area under the concentration-time curve (AUC). The primary objective was to demonstrate that PK-guided 5-FU dosing improves the ability to achieve a target AUC within four cycles of therapy. The secondary objective was to demonstrate reduced incidence of 5-FU-related toxicities. Results: At cycles 1 and 4, 27.7% and 46.8% of patients achieved the target AUC (20–25 mg × hour/L), respectively (odds ratio [OR]: 2.20; p = .046). Significantly more patients were within range at cycle 4 compared with a literature rate of 20% ( p < .0001). Patients had significantly higher odds of not being underdosed at cycle 4 versus cycle 1 (OR: 2.29; p = .037). The odds of a patient being within range increased by 30% at each subsequent cycle (OR: 1.30; p = .03). Less grade 3/4 mucositis and diarrhea were observed compared with historical data (1.9% vs 16% and 5.6% vs 12%, respectively); however, rates of grade 3/4 neutropenia were similar (33% vs 25%–50%). Conclusion: PK-guided 5-FU dosing resulted in significantly fewer underdosed patients and less gastrointestinal toxicity and allows for the application of personalized colorectal cancer therapy in the community setting. Abstract : A paucity of data exists on pharmacokinetically guided 5 fluorouracil (5-FU) dosing in the community setting. This multicenter study demonstrated the practicality of using a simple methodology to guide 5-FU dosing in the community setting and resulted in significantly fewer underdosed patients and less gastrointestinal toxicity.